CSU meat school, no. 3: Meat quality; Food safety starts on the farm: the last mile and biosecurity for small producers - Sullins, Martha, speaker; Thistlethwaite, Rebecca, speaker; Martin, Jennifer, speaker; Pfannenstiel, Michele, speaker; Colorado State University. Extension, producer (Colorado State University. Libraries, 2019)
Meat School overview: November 13 - Production: disease prevention, finishing, carcass quality, grading, quality assurance and safety from farm to harvest.
Meat quality
Food safety starts on the farm: the last mile and biosecurity for small producers
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Animal industry; Meat industry and trade; Food industry and trade -- Safety measures; Biosecurity